Crypt-tag authentication in NFC implementation for medicine data management - Zainal Abidin, Zaheera; Zakaria, Nurul Azma; Harum, Norharyati; Baharon, Mohd Rizuan; Mat Ariff, Nor Azman; Abal Abas, Zuraida; Hong, Ee-Song; Ayop, Zakiah (Science and Information Organization, 2018)
This study focus on the implementation of expiry date detection for medicine using RFID in the health care industry. The motivation for doing this research is the process of searching for the expired medicine is a time consuming and lack of security features included in current NFC implementation. Therefore, the objective of this research is to study the RFID technology used for detecting medicine expiry product and to develop a new system that integrated NFC with authentication feature. Moreover, the problem of current data management for medicine still using manual or barcode system that lead to inconsistency, easy duplication and human error. Here, the NFC is chosen, due to smaller distance of signal coverage, since less interference and the time spending for sniffing activity by the hacker can be reduced. The system is developed using C#, SQLite, Visual Studio, NFC Tag and NFC reader (ACR122UA9). Experiments have shown that the proposed system has produced medicine expiry date system and only authorized person in charge can monitor the medicine. The impact of the proposed system produces safer, greener and easier environment for better medicine data management. The significance of this study gives a medicine expiry date detection system for health care.